Enhancing Education Management for Green Development in Engineering Programs: Strategies, Challenges, and Outcomes - Eshbayev, Oybek (GREEN ECONOMY AND DEVELOPMENT, 2023)
in the context of the global imperative for sustainable development, engineering programs play an important role in the development of green practices and principles. This study aims to explore the strategies, challenges, and outcomes associated with improving the management of education for green development in engineering programs. The research requires a comprehensive approach that includes both qualitative and quantitative methods to collect data from multiple stakeholders, including students, faculty, and industry professionals. Through a series of interviews, surveys, and document analysis, key strategies for integrating green concepts into engineering curricula are identified. These strategies include curriculum redesign, faculty development, collaboration with industry, and the incorporation of sustainable technologies and practices in labs and projects. However, a number of challenges, such as resistance to change, resource constraints, and limited faculty expertise in green technologies, hinder the implementation of these strategies. Despite these challenges, our research shows positive results in the adoption of strategies, including increasing awareness and knowledge of sustainability among students, increasing the relevance of engineering programs to industry, and fostering a green mindset among graduates. The research findings provide valuable insights and recommendations for educational management in engineering programs seeking to adopt green development principles. The study analyzes the importance of proactive measures to solve problems and advocates the need for continuous support and professional development of teachers. In addition, it explores the importance of fostering collaboration between academia and industry to ensure the integration of true green practices into engineering education. By improving education management for green development, engineering programs can significantly contribute to sustainable and environmentally conscious practices, shaping future engineers as catalysts for positive change.